Effect of graphite particles on improving tribological properties Al-16Si-5Ni-5Graphite self-lubricating composite under fully flooded and starved lubrication conditions for transportation applications. Issue 1 (October 2016) - Omrani, Emad; Moghadam, Afsaneh; Algazzar, Mahmoud; Menezes, Pradeep; Rohatgi, Pradeep
Abstract The piston ring and cylinder liner materials encounter challenges under limited lubricated conditions leading to high friction and wear. Although, several materials, from cast iron to composite materials, have been proposed in the past, these materials still exhibit poor tribological properties under limited lubricated conditions and there is a need to develop materials that show enhanced tribological properties under limited lubricated conditions. Hence, in the present investigation, Al-16Si-5Ni-5Graphite composite was successfully synthesized as a substitute material for steel in piston ring materials. Different tribometers were used to analyze the tribological properties of aluminum composite reinforced by graphite and steel specimens in lubrication condition and limited lubricated conditions. Under limited lubrication conditions, steel specimen showed higher coefficient of friction (COF) than the Al-16Si-5Ni-5Graphite specimen. Besides, the steel specimen exhibited an increase in COF with increasing applied normal load, while the Al-16Si-5Ni-5Graphite showed reduction in COF with increasing applied normal load. The value of COF and acoustic emission (AE) for steel was constant at lower range of normal loads up to 705 N and thereafter, a sudden increase in both COF and AE signal was observed. On the other hand, Al-16Si-5Ni-5Graphite composite did not exhibit any variations in COF and AE even beyond the transition load of 750 N and remained constant up to the normal load of 990 N. Such trend of results suggested that the Al-16Si-5Ni-5Graphite composite showed superior tribological performance when compared to steel under limited or boundary lubrication conditions. In addition, results show that composite has good tribological properties under limited lubricated conditions due to presence of graphite particles in the composites that graphite particles act as solid lubricant on worn surfaces.